At Ansha's : Life in the Spirit Mosque of a Healer in Mozambique - Trentini, Daria (Book collections on Project MUSE., 2021)
"At Ansha's takes the reader inside the spirit mosque of a female healer in Nampula, northern Mozambique. It is here that Ansha, a Makonde spirit healer, heals the resisting ailments of her patients, discloses pieces of her story of affliction and healing, and engages the world outside her mosque. We come to know Ansha's experiences as revolutionary and migrant, her religious trajectories, family, the healers who cured her, the spirits who possessed her, and her declining health. We follow Ansha's shifts in her life and work in the mosque as these intersect with the visible and invisible borders of Mozambique and of its fraught history. Confronting events in her life and in the mosque during between 2009 and 2016, Ansha invites us to make meaning with her, as we sit in her mosque, and engage with her family, spirits, friends, patients, and world"--